Sistem Administrasi Pengelolaan Data Perkara Di Komite Penyelidikan dan Pemberantasan Korupsi Kolusi dan Nepotisme (KP2KKN) Jawa Tengah Berbasis Web (Information Technology and Telematics, 2014)
Abstract - Many Action of corruption, collusion and nepotism has been done by all coruptor . To get informationabout the data, committee take sources from the newspaper and uploaded on their privacy site, so that the visitorsshould visit that magazine’s owner site one by one. While the arrangement of report data that submitted and the casewhich controlled still using manual way.This issues can be solved by creating new system which can organize the case of data and ca n be use to display forthe visitors. This system will build with PHP and MvSQL. The system which created can displays the data ofinformation, the detail case, adding and organize case of data or ne case, search the data based on country.Keywords: Administrator website, Data corruption case.